The Influence of E-Service Quality and E-Trust on the Level of E-Loyalty of Gojek Application Users in the Cirebon Region - Kurniawan, Deni; Romdonny, Jefry; Dedu, May (Indonesian Journal of Advanced Research, 2026)
This study is aimed at analyzing the impact of e-service quality and e-trust on the e-loyalty of  Gojek application users in the Cirebon Region. The method used was quantitative descriptive, with a survey of 150 active Gojek users using purposive sampling. The data was analyzed through Partial Least Squares (PLS) using SmartPLS. The results indicated that e-service quality had a positive and significant influence on e-loyalty (path coefficient = 0.391; p = 0.001), while e-trust had a more dominant influence (path coefficient = 0.452; p = 0.000). Simultaneously, two variables exert a substantial influence on e-loyalty with an R-Square of 0.650, meaning that 65% of user loyalty variations are explained by both variables. Improving the quality of digital services and strengthening user trust are key strategies to maintain Gojek's loyalty in an increasingly competitive market.